Acerca de la política lingüística, bilinguismo y biculturalidad y educación - Jung, Ingrid (1987)
In the department of Puno, just as in other Andean regions where similar experiences have been carried out, we find a surprising phenomenon at first glance when we analyze the opinions about bilingual education by the different groups involved. Roughly speaking, it can be stated that parents are very skeptical about teaching in the mother tongue, advancing arguments such as "we already know our language, why teach it; but we have to learn Spanish". Teachers somewhat share this point of view, with the difference that they reject teaching in the mother tongue because "it is not a language, just a dialect without writing".